2015
DOI: 10.1016/j.bjhh.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Torque teno virus in healthy donors of Paraná State, southern Brazil

Abstract: ObjectiveTo determine the prevalence of the Torque teno virus in healthy donors in the northern and northwestern regions of the state of Paraná, southern Brazil.MethodsThe Torque teno virus was detected by a nested polymerase chain reaction using a set of oligoprimers for the N22 region.ResultsThe prevalence of the virus was 69% in 551 healthy blood donors in southern Brazil. There was no statistically significant difference between the presence of the virus and the variables gender, ethnicity and marital stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
2
10
1
2
Order By: Relevance
“…Similarly, the difference in prevalence between individuals who had a history of receiving blood transfusions and those who did not (90.5% and 95.7%, respectively) is also small in magnitude and in the opposite direction to that expected if blood transfusions were responsible for introducing TTV to the subjects. Similar to our findings here, a number of studies failed to find a significant relationship between TTV prevalence and subject characteristics in other countries, including Egypt [41], Russia [42], Brazil [40], Iran [23] and Qatar [10]. Conversely, a number of studies reported a significant association between TTV prevalence and subject attributes in other countries, including: gender [sic] in the UAE [43]; blood transfusion history in Iran [23]; age in the UK [44], China [19], Brazil [40] and Qatar [10]; and obesity in Romanian women [45].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, the difference in prevalence between individuals who had a history of receiving blood transfusions and those who did not (90.5% and 95.7%, respectively) is also small in magnitude and in the opposite direction to that expected if blood transfusions were responsible for introducing TTV to the subjects. Similar to our findings here, a number of studies failed to find a significant relationship between TTV prevalence and subject characteristics in other countries, including Egypt [41], Russia [42], Brazil [40], Iran [23] and Qatar [10]. Conversely, a number of studies reported a significant association between TTV prevalence and subject attributes in other countries, including: gender [sic] in the UAE [43]; blood transfusion history in Iran [23]; age in the UK [44], China [19], Brazil [40] and Qatar [10]; and obesity in Romanian women [45].…”
Section: Discussionsupporting
confidence: 90%
“…Within the relatively narrow confines of Jordan (the farthest samples are less than 450 km apart), no significant differences in prevalence among regions were detected. This is to be contrasted with a number of studies of much larger countries which reported geographical variation in TTV prevalence (3%-72% in India [36,37]; 2%-34% in Iran [9,23] and 6%-85% in Brazil [38][39][40]). The fact that these wide ranges were reported by different studies per country, leaves open the possibility that the observed within-country difference in prevalence might be at least partly due to variation in methodology (sampling scheme, sets of primers used, year of study, etc.)…”
Section: Discussionmentioning
confidence: 60%
“… доноры крови [23,[67][68][69];  больные гемофилией [70][71][72];  пациенты с многократными гемотрансфузиями [73][74][75][76];…”
Section: пути передачиunclassified
“…Распространенности инфекции способствует заражение крови и ее продуктов вирусом TT [23,67,68,73,78,88,89]. Так, инфицированность продуктов крови и факторов свертывания VIII и IX, по данным P. Simmonds и соавт., составляет 44-56 % [88].…”
Section: пути передачиunclassified
“…In this article, the authors demonstrated the prevalence of the TTV in healthy donors in the northern and northwestern regions of the state of Paraná, southern Brazil, by nested PCR using a set of primers for the N22 region. 9 …”
mentioning
confidence: 99%